Biopsychosocial Management of Female Sexual Dysfunction: A Pilot Study of Patient Perceptions From 2 Multi-Disciplinary Clinics. Issue 3 (19th May 2018) - Rullo, Jordan; Faubion, Stephanie S.; Hartzell, Rose; Goldstein, Sue; Cohen, Deborah; Frohmader, Karla; Winter, Ashley G.; Mara, Kristin; Schroeder, Darrell; Goldstein, Irwin
Abstract: Background: Sexual dysfunction is often complex and biopsychosocial. Traditional sexual health care management involves individual providers not in a multi-disciplinary setting. A multi-disciplinary team may consist of a medical provider, pelvic floor physical therapist, and sex therapist. Aim: The aim was to explore the patient perceptions of benefit from management of their sexual dysfunction by a biopsychosocial multi-disciplinary team. Methods: A survey was e-mailed to women patients seen by multi-disciplinary teams at 2 different settings: San Diego Sexual Medicine or Mayo Clinic Women's Health Clinic during a 27-month period. Data are reported using summary statistics for age and count for remaining survey responses. Cochran-Armitage tests for trend were used to compare pre- and post-comfort levels. Outcomes: Main outcome measures included perceived benefit of being managed in a team-based model of care, level of benefit and satisfaction from each provider, and difference from pre-conceived level of comfort to actual comfort after each provider visit. Results: 89 of 270 e-mailed surveys were analyzed. Patient populations (mean age 47.6, range 23–77 years) were similar between sites. Overall, 82% of respondents reported moderate/great benefit from the team-based model; 72.1% reported management by all 3 providers valuable/extremely valuable; and 84.3% were somewhat/very satisfied with the model. Women endorsed specific ways in which they benefitted from the team-based model including: improved sexual function (58.1%), feeling validated (72.1%) and listened to (62.8%), that they better understood their health concerns (65.1%), that their partner better understood their health concerns (46.5%), and feeling normal (46.5%). There were no significant differences between the 2 clinics in terms of patient-perceived benefit, value, or satisfaction. Conclusions: The team-based model of care for management of sexual dysfunction in women including a medical provider, physical therapist, and sex therapist is associated with patient-perceived benefit, satisfaction, and value.